Pengembangan Sistem Informasi Pemesanan Tiket Konser Malang Berbasis Web - Ratih Pinandita; Fajar Pradana; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Web-based Concert Ticket Booking System is a platform specifically designed for booking concert tickets in Malang. This concert ticket booking system aims to make it easy to buy concert tickets through the website so all the users can easily booked concert tickets. This system helps to connect the buyers and sellers to buying and selling concert tickets. The sellers can easily promote Malang concerts through this website and for the buyers who orders concert tickets easily through the website. The advantage of the system from the buyer side is being able to search concert tickets by inputting words in the search column. In the search feature, this system uses Text preprocessing to process data into a term index and this system uses two calculation methods, namely, Tf-Idf (Term Frequency Inverse Document Frequency) is used to calculate the weight of each word contained in concert information that contains a description of the concert, day and date & time and Cosine similarity is used to calculate the similarity value between sentences based on the calculation of the TF-IDF. From the calculation of the two methods you can find a concert description that matches or approaches the inputted word. So that by using these calculations it will be easier to find the desired concert. In addition to being able to search, buyers can also order tickets, make payments and if they have done making payments, the buyer will get a notification via email.